Shallow water tanaidaceans (Crustacea: Peracarida: Tanaidacea) from New Caledonia and the Loyalty Islands - Bamber, Roger N. (Zootaxa, 2006)
The Pacific collections by the MUSORSTOM campaigns of the Paris Museum over the last twenty years include a total of four species of Tanaidacea from shallow waters of the New Caledonia region and all new to science. These species are described herein, one in the family Tanaidae, Zeuxo (Parazeuxo) cloacarattus, and three in the family Leptocheliidae, viz. Pseudoleptochelia bulbus, the second Pacific species recorded for this genus, a species of the Leptochelia minuta agg. represented only by males, and a species with unusual cheliped carpus morphology which is placed in a new genus as Konarus cheiris.